Coping Beyond Cancer: Exploring Fear of Recurrence in Colorectal Cancer Survivors—A Pilot Investigation - Emily M Su; Steve Paciorek; Erica L Laipply; Anuja L Sarode (HCA Healthcare Journal of Medicine, 2026)
Background Evidence is limited on the fear of cancer recurrence (FCR) among colorectal cancer (CRC) survivors in the US, especially regarding patterns and trends of post-recovery coping mechanisms. This pilot mixed-methods study quantified FCR, examined its associations with Brief COPE domains, and contextualized coping through qualitative analysis. Methods Twenty-three patients who successfully underwent CRC surgery were included in this pilot study. Fear of cancer recurrence was measured using the FCR Inventory (FCRI) Short Form, and coping strategies were assessed with the Brief Coping Orientation to Problems Experienced (COPE) survey. Descriptive statistics summarized participant characteristics, FCR, and COPE scores. Spearman correlation and univariate linear regression analyses were used to examine the associations within coping strategies and with FCR. Qualitative data from the FCRI and Brief COPE were presented as direct participant quotations. Results The cohort was predominantly female (70%) and white (78%), with a mean age of 66. Elevated levels of FCR (scores ≥ 12) were reported by 70% of participants. Behavioral disengagement (detachment, reduced effort) was associated with higher FCR (β = 3.1; P = .03). Significant positive and negative correlations were observed within several COPE domains. Qualitative findings showed that faith, family support, and acceptance were notable coping mechanisms. Participants reported external reminders, such as treatment side effects and medical appointments, and internal factors, such as interpersonal interactions, as significant FCR triggers. Conclusion This study identified a high level of FCR among CRC survivors in the US and underscored the complex interplay between coping strategies and FCR. The findings highlighted the need for tailored interventions and further research to enhance the understanding and management of FCR in this population.